Investigating the Moderating Role of Cognitive Flexibility in the Relationship Between Maltreatment and Emotion Regulation in Adolescence With Childhood Trauma - Ameneh Bozorgi Kazerooni; Niloufar Gholamipour (Gonabad University of Medical Sciences, 2023)
Background: Adolescence is a developmental period when adverse childhood experiences significantly impact the individual because of the changes in brain structure and functioning. This research aims to investigate the relationship between maltreatment and emotion regulation with the moderating role of cognitive flexibility in adolescence with childhood trauma. Methods: This was a descriptive-correlational study. The study population consisted of all adolescents who were referred to the psychological and psychiatric disorders clinics and medical clinics of Shiraz City, Iran, in the spring semester of 2021. The population included 250 individuals, of which 175 were selected as the sample of the research via the simple random sampling method according to the Morgan Table. The research tools were the childhood trauma questionnaire, the cognitive flexibility questionnaire, the psychological maltreatment scale, and the emotional regulation scale. After completing the questionnaires, the data were entered into the SPSS software, version 23, and analyzed using descriptive and inferential statistics. The Pearson correlation test and the regression method were used to analyze the data. Results: The results showed a significant negative correlation between maltreatment with emotion regulation (r=-0.531, P<0.001). The results showed that the interaction of these 3 variables indicated that cognitive flexibility has a moderating role in the relationship between maltreatment and emotional regulation (β=-0.90, P<0.01). Moreover, the results indicated that the relationship between maltreatment and emotion regulation in adolescence with high flexibility is higher than in individuals with low flexibility. Conclusion: This study provides evidence that cognitive flexibility can act as a moderator when considering the impact of trauma. The developed task could provide a novel way to assess this flexibility within an emotional context.